Analysis of evidence. - Anderson, Terence (Law in context., 2005)
A rigorous introduction to the construction and criticism of arguments about questions of fact, and to the marshalling and evaluation of evidence in litigation. Most chapters have been rewritten; the treatment of fact investigation, probabilities and narrative has been extended; and new examples and exercises have been added.